Highly Efficient Adsorption of Phenylethanoid Glycosides on Mesoporous Carbon - Xu, Helin; Pei, Wenjing; Li, Xueqin; Zhang, Jinli (Frontiers in Chemistry, 2019)
PhGs are the major active compounds of Cistanche tubulosa, and it is extremely desirable for obtaining high purification of PhGs by adsorption from their extracts. To explore highly efficient adsorption of PhGs, a novel adsorption material for the efficient separation and purification of phenylethanoid glycosides (PhGs) from Cistanche tubulosa was explored. The three mesoporous carbons of ordered mesoporous carbon (CMK-3), disordered mesoporous carbon (DMC) and three-dimensional cubic mesoporous carbon (CMK-8) were compared for adsorption of PhGs. Meanwhile, adsorption isotherms, adsorption kinetics, and the optimization of adsorption conditions were investigated. The results indicated that CMK-3 showed the highest adsorption capacity of 358.09 ± 4.13 mg/g due to its high specific surface area, large pore volume and oxygen-containing functional groups. The experimental data can be accurately described using the Langmuir model and pseudo-second-order model. The intra-particle diffusion model suggested that the rate-limiting steps of adsorption were intra-particle diffusion.